Aplikasi Pembelajaran Hukum Pidana Umum Untuk Generasi Muda Berbasis Android - Irwandi, Irwandi; Rizki, Sestri Novia (Journal Information System Development (ISD), 2020)
Law is a rule that is a norm made by aiming to regulate every human behavior for example keeping order, fairness, and preventing chaos. Today's young generation is very lack of science about the law, legal learning is a fairly elusive and boring lesson and also the science of law is considered low and many are violating or defying the law, younger generations nowadays smore often play smartphones than on reading books about the law that is so thick. So they are more interested in learning the law with Android based learning media. Game application also aims to fill free time or rest time. In addition to entertainment or pleasure games also serve as learning media and can hone skills, intelligence in overcoming a problem found in a game. Besides because this game combines the learning and playing side, this game can also be used to attract the attention of the younger generation to continue to learn about the law, especially in the case of theft game application created and designed with the aim that the generation of easily more pleased to learn law on the case of theft with learning media games.Â  The preparation of this research in making games with waterfall method (Reqriutment, Design, Implementation, Verification and Maintenance) and to analyze using Unified Modeling Language (UML) including Use Case Diagram, Activity Diagram, Sequence Diagram, Class Diagram. The learning games themselves will be developed based on Android or intended for mobile/Smartphone users. Method used in the creation of game applications using waterfall method. This game is played by one person in this game there are several Theory and quiz. Based on the test results of the general criminal law Learning games for Android based youth using CONSTRUCT2 software that this Game application can be inserted on smartphones with the minimum operating system Android.Keywords: android, hukum, pidana, game, kuis